How do household members share tasks across the agrifood system in Surkhet, Nepal? - Banerjee, Archis; Scott, Samuel P.; Kumar, Neha; Quisumbing, Agnes R.; Tomar, Anindya; Parvin, Aklima; Menon, Purnima; Kishore, Avinash (CGIAR System Organization, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA) district agrifood systems assessment aims to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It is designed to be a multi-year assessment. Using data collected in March–April 2023, this data note describes how different tasks are performed and shared within the household and how female respondents within these households perceive the notion of leisure, work pressure, and support with chores from other household members. This is one of a set of data notes that, together, provide a holistic picture of theagrifood system in the district.